2009
DOI: 10.1007/s11255-009-9533-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between total/free prostate-specific antigen and prostate volume in Chinese men with biopsy-proven benign prostatic hyperplasia

Abstract: Although tPSA significantly correlated with PV in Chinese men with biopsy-proven BPH, the correlation between fPSA and PV was much stronger, and fPSA performed significantly better than tPSA at predicting thresholds of PV. fPSA may be used to estimate PV and could be a useful tool in making therapeutic decisions in Chinese men with BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 17 publications
3
27
2
Order By: Relevance
“…The ROC curves revealed that the efficacy of fPSA at predicting threshold prostate sizes (30, 40, and 50 mL) showed AUC ranging from 0.72 to 0.75, denoting better discrimination of PV than that of tPSA [18]. …”
Section: Discussionmentioning
confidence: 99%
“…The ROC curves revealed that the efficacy of fPSA at predicting threshold prostate sizes (30, 40, and 50 mL) showed AUC ranging from 0.72 to 0.75, denoting better discrimination of PV than that of tPSA [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Ornstein et al 8 reported that among 70 men with biopsy-proven BPH, %fPSA, but not PSA, was significantly correlated with TPV in patients with PSA levels ranging from 2.6 to 9.9 ng ml 21 , indicating a predictive role of fPSA for TPV. Mao et al 7 reported that fPSA was a more accurate predictor of TPV than PSA in 286 Chinese men with biopsy-proven BPH. In the current study, the correlation coefficient of the formula incorporating PSA and %fPSA with TPV (R50.56) was equal to that of the formula using only fPSA with TPV (R50.56).…”
Section: Discussionmentioning
confidence: 99%
“…This cut-off point has been used in previous studies, not only for Western populations 17,18 but also for Asian populations. 7 Using the TMDU data set, significant and independent predictors of TPVs greater than 40 ml were identified by univariate and multivariate analyses using a backward stepwise logistic regression. Incorporating all of the significant predictors, a logistic regression-based nomogram was developed.…”
Section: Creation Of the Equation For Predicting Prostate Volumementioning
confidence: 99%
See 2 more Smart Citations